Three-dimensional-printed cardiac prototypes aid surgical decision-making and preoperative planning in selected cases of complex congenital heart diseases: Early experience and proof of concept in a resource-limited environment - Mahesh Kappanayil; Nageshwara Rao Koneti; Rajesh R Kannan; Brijesh P Kottayil; Krishna Kumar (Wolters Kluwer Medknow Publications, 2017)
Introduction: Three-dimensional. (3D) printing is an innovative manufacturing process that allows computer.assisted conversion of 3D imaging data into physical "printouts" Healthcare applications are currently in evolution. Objective: The objective of this study was to explore the feasibility and impact of using patient-specific 3D-printed cardiac prototypes derived from high.resolution medical imaging data. (cardiac magnetic resonance imaging/computed tomography. [MRI/CT]) on surgical decision-making and preoperative planning in selected cases of complex congenital heart diseases. (CHDs). Materials and Methods: Five patients with complex CHD with previously unresolved management decisions were chosen. These included two patients with complex double.outlet right ventricle, two patients with criss-cross atrioventricular connections, and one patient with congenitally corrected transposition of great arteries with pulmonary atresia. Cardiac MRI was done for all patients, cardiac CT for one; specific surgical challenges were identified. Volumetric data were used to generate patient-specific 3D models. All cases were reviewed along with their 3D models, and the impact on surgical decision-making and preoperative planning was assessed. Results: Accurate life-sized 3D cardiac prototypes were successfully created for all patients. The models enabled radically improved 3D understanding of anatomy, identification of specific technical challenges, and precise surgical planning. Augmentation of existing clinical and imaging data by 3D prototypes allowed successful execution of complex surgeries for all five patients, in accordance with the preoperative planning. Conclusions: 3D-printed cardiac prototypes can radically assist decision-making, planning, and safe execution of complex congenital heart surgery by improving understanding of 3D anatomy and allowing anticipation of technical challenges.